所以f(1)+f(3)+f(5)+…+f(11)
=sin
π |
6 |
3π |
6 |
5π |
6 |
7π |
6 |
9π |
6 |
11π |
6 |
=
1 |
2 |
1 |
2 |
1 |
2 |
1 |
2 |
∴f(1)+f(3)+f(5)+…+f(101)
=8×(sin
π |
6 |
3π |
6 |
5π |
6 |
7π |
6 |
9π |
6 |
11π |
6 |
π |
6 |
3π |
6 |
5π |
6 |
=sin
π |
6 |
3π |
6 |
5π |
6 |
=
1 |
2 |
1 |
2 |
故答案为:2.
nπ |
6 |
π |
6 |
3π |
6 |
5π |
6 |
7π |
6 |
9π |
6 |
11π |
6 |
1 |
2 |
1 |
2 |
1 |
2 |
1 |
2 |
π |
6 |
3π |
6 |
5π |
6 |
7π |
6 |
9π |
6 |
11π |
6 |
π |
6 |
3π |
6 |
5π |
6 |
π |
6 |
3π |
6 |
5π |
6 |
1 |
2 |
1 |
2 |